P361 PREPARE-IBD: Physician Responses to disease Flares and Patient Adaptation in Relation to Events in Inflammatory Bowel Disease during the COVID-19 pandemic: A multicentre cohort analysis. (21st January 2022) - Saifuddin, A; Kent, A; Mehta, S; Hicks, L; Gonzalez, H; Segal, J; Brooks, M; Subramanian, S; Bhala, N; Conley, T; Patel, K; Lamb, C; et al.
Abstract: Background: The COVID-19 pandemic continues to pose complex problems across Europe and the world, with rising numbers of infections and the ongoing need for drastic public health interventions. This is difficult for patients with immune-mediated disorders like Inflammatory Bowel Disease (IBD), where immunosuppressive medications may affect susceptibility to serious infection. It was particularly challenging for physicians and patients during the first wave of the pandemic, when it was unclear whether anti-inflammatory flare treatment should be adapted to reduce infection risk, whilst trying to ensure symptomatic control and avoid admission to overwhelmed hospitals. Despite the development of various IBD / COVID-19 databases, the treatment adaptations and outcomes of patients experiencing IBD flares during the COVID-19 pandemic remain undefined. We aimed to compare IBD management and outcomes between pandemic and pre-pandemic cohorts. Methods: An observational cohort study was performed, comprising patients who contacted IBD teams for a symptom flare between March – June, 2020 in, 60 National Health Service trusts in the United Kingdom. Data were compared to a pre-pandemic cohort after propensity-matching for age and disease severity. Statistical analyses were performed using R (version, 4.1.0, Vienna, Austria). Results: In total, 3728 patients in the pandemic (n=1864) and pre-pandemic (n=1864) cohorts were included. The principal findings were reduced systemic corticosteroid prescription during the pandemic in both Crohn's disease (prednisolone: pandemic, 199/752, 26.5% vs, 263/708, 37.1%; p<0.001) and ulcerative colitis (UC) (prednisolone: pandemic, 372/1112, 33.5% vs, 470/1156, 40.7%, p<0.001), with increases in poorly bioavailable oral corticosteroids in Crohn's (pandemic, 117/752, 15.6% vs, 48/708, 6.8%; p<0.001) and UC (pandemic, 131/1112, 11.8% vs, 60/1156, 5.2%; p<0.001). Ustekinumab (Crohn's and UC) and vedolizumab (UC) treatment also significantly increased during the pandemic. Three-month steroid-free remission was similar in both Crohn's (pandemic, 175/616, 28.4% vs, 195/608, 32.1%; p=0.17) and UC (pandemic, 312/858, 36.4% vs, 404/1006, 40.2%; p=0.095). The, 65 patients experiencing a flare and COVID-19 were more likely to have moderate-to-severely active disease at three months compared to those with a flare alone. Conclusion: Despite several treatment adaptations during the pandemic, steroid-free outcomes were comparable to pre-pandemic levels, though patients with a flare and COVID-19 experienced worse outcomes. These findings have implications for IBD management during future waves or pandemics